Physico-Chemical and Qualitative, Quantitative Chemical Compounds Analysis of Pleurotus florida in Thanjavur, Tamilnadu, India.: Life Sciences-Botany - Ganesan, Gayathri; Selvam, Gomathi; Varatharasu, Ambikapathy; Annamalai, Panneerselvam (International Journal of Life Science and Pharma Research, 2023)
An extensive range of lignocellulosic waste is used in mushroom growing, which is recognized as a very successful way to recycle agricultural waste and make food. Primary and secondary metabolites analysis is fundamental for further pharmaceutical studies. In this present study, physico-chemical analysis viz., moisture content, ash value, crude fat, crude fibre content, carbohydrates and protein content were evaluated in Pleurotus florida. Phytochemical analysis of inPleurotusflorida was done using four different solvents like hexane, chloroform, methanol and aqueous, using a standard protocol. The result of the present study showed moisture content (7.22±0.03mg/g), ash value (3.20±0.00 mg/g), crude fat (4.50±0.00 mg/g), crude fibre content (2.81±0.08 mg/g), carbohydrates (0.18±0.06 mg/g) and protein (0.36±0.11 mg/g). Qualitative analysis of P. florida showed the presence of alkaloids, anthraquinone, flavonoid, glycosides, phenol, saponin, steroid, tannin and terpenoid. The above compound is further estimated quantitatively. Aqueous extract of P.florida showed alkaloid (0.42±0.02 mg/g), anthraquinone (0.65±0.00 mg/g), flavonoid (9.19±0.00 mg/g), glycosides (3.40±0.04 mg/g), phenol (4.74±0.00 mg/g), saponin (12.1±0.03 mg/g), tannin (26.1±0.00 mg/g) and terpenoid (0.73±0.01 mg/g). Methanolic extract showed alkaloid (2.91±7.85 mg/g), anthraquinone (3.48±0.06 mg/g), steroid (2.34±0.01 mg/g), tannin (21.5±0.00 mg/g) and terpenoid (0.45±0.03 mg/g). The other compounds like alkaloid (0.78±0.00 mg/g), anthraquinone (1.79±0.01 mg/g), flavonoid (10.9±0.04 mg/g), glycosides (12.8±0.05 mg/g), phenol (39.3±0.00 mg/g), saponin (35.8±0.00 mg/g), steroid (3.47±0.00 mg/g) and terpenoid (0.34±0.02 mg/g) were showed in chloroform extract of P.florida. In hexane extract, an alkaloid (0.59±0.03 mg/g), saponin (2.58±0.00 mg/g), tannin (426±0.00 mg/g) and terpenoid (0.38±0.01 mg/g) were estimated. Finally, the secondary metabolites were employed as an ontology tool (Protégé), and the outcomes were displayed in diagrammatic form. Protégé tool is one alternative technology for using smart art diagrams like bar and pie diagrams in future quantitative analysis response compounds for further immune system development studies.